Supply chain agility: a systematic review of definitions, enablers and performance implications. Issue 2 (29th April 2020) - Al Humdan, Eias; Shi, Yangyan; Behnia, Masud
Abstract : Purpose: Supply chain agility (SCA) has recently received considerable attention in the literature and in practice. Despite its popularity, the concept of SCA seems to be vaguely defined and loosely structured. More specifically, definitional ambiguity and conceptual fragmentation have prevented the concept of SCA from reaching its full potential. The time is ripe to address these issues through a systematic literature review. Design/methodology/approach: A review and synthesis of the literature on SCA was undertaken. The authors selected 56 top-tier related articles for further analysis after applying rigorous filtering procedures. Findings: The results of the review confirm that several key themes surround SCA's definition and enablers. In addition, consensus needs to be reached in terms of its performance dimensions and measures. Accordingly, this study constructed an encompassing definition, scrutinized SCA enablers and outcomes and thus developed an original framework for SCA, providing a unique conceptual contribution. Several research directions were also addressed accordingly. Originality/value: The novelty of this research lies in the selection of highly recognized publications. It also provides an encompassing definition of SCA, consolidates its enablers for better communication and synthesizes its performance implications.